Environmental risk assessment : a toxicological approach - Simon, Ted (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
'This book explains how environmental risk assessment in particular is of increasing importance as a means of seeking to address the potential effects of chemicals in the environment in both the developed and developing world'--
Includes bibliographical references and index.
Keywords: Environmental risk assessment; Environmental toxicology